2020
DOI: 10.1016/j.lfs.2020.117583
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Melatonin as a potential adjuvant treatment

Abstract: This article summarizes the likely benefits of melatonin in the attenuation of COVID-19 based on its putative pathogenesis. The recent outbreak of Journal Pre-proof

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
621
0
31

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(672 citation statements)
references
References 72 publications
5
621
0
31
Order By: Relevance
“…By increasing the activity of the anti-oxidative enzymes, these beneficial effects of OEA can be justified (33,34). It has been suggested that excessive inflammation, oxidation and an increased…”
Section: Oleoylethanolamide and Sars-cov-2 Infectionmentioning
confidence: 99%
“…By increasing the activity of the anti-oxidative enzymes, these beneficial effects of OEA can be justified (33,34). It has been suggested that excessive inflammation, oxidation and an increased…”
Section: Oleoylethanolamide and Sars-cov-2 Infectionmentioning
confidence: 99%
“…In animal models, this natural hormone has been shown to improve acute lung injury by acting as a direct antioxidant and via melatonin receptor activation. The protective effect of Ramelteon (an MRA) against ventilatoreinduced lung injury, has recently been shown to depend on the upregulation of Interleukin (IL-10) in rats [5].…”
mentioning
confidence: 99%
“…Sleep, a circadian behavioral manifestation of major regulatory homeostatic mechanisms such as those associated with immunity, has also been shown to interact with host defenses at the molecular and cellular levels. Indeed, extensive literature has indicated the important role of homeostatic sleep in innate and adaptive immunity (46). Furthermore, there are clear reciprocal dependencies between sleep duration and quality and the immune responses against viral, bacterial, and parasitic pathogens, the latter altering in turn sleep patterns (46).…”
Section: Sleep and Sars-cov 2 Infectionmentioning
confidence: 99%
“…Indeed, extensive literature has indicated the important role of homeostatic sleep in innate and adaptive immunity (46). Furthermore, there are clear reciprocal dependencies between sleep duration and quality and the immune responses against viral, bacterial, and parasitic pathogens, the latter altering in turn sleep patterns (46). Thus, it is likely that improved sleep quality and duration in the population may mitigate the propagation and severity of disease induced by SASRS-Cov-2 infection.…”
Section: Sleep and Sars-cov 2 Infectionmentioning
confidence: 99%